Research Trends in Empowering Leadership and Innovative Work Behavior in Business Organizations: A Bibliometric and Systematic Literature Review - Irhamna, Muthia; Soeling, Pantius Drahen (Dinasti International Journal of Economics, Finance & Accounting, 2026)
Empowering leadership is a leadership approach that is gaining increasing attention because of its ability to encourage innovative work behavior (IWB) employees. Although the number of publications on this topic continues to increase, research results are still scattered across various contexts, theories, and research methods, requiring a comprehensive synthesis. This study aims to analyze the development of research on empowering leadership And innovative work behavior, identifying the theory used, dominant mediating and moderating variables, research methods, research context, and identifying gaps and future research agendas. The research uses a qualitative approach. Systematic Literature Review(SLR) combined with bibliometric analysis. Articles were obtained from the Scopus database with a publication period of 2021–2026. The selection process was conducted based on PRISMA guidelines, resulting in 14 articles meeting the inclusion criteria for further analysis. The analysis results indicate that Empowerment Theory, Psychological Empowerment Theory, And Social Cognitive Theory is the most widely used theory. The dominant mediating variable is psychological empowerment, employee empowerment, and self-efficacy, while research on moderating variables is still relatively limited. Most studies use quantitative methods with SEM and PLS-SEM approaches and focus on the business and organizational sectors. Furthermore, bibliometric analysis indicates new research trends focusing on communication, digital capabilities, and digital transformation. Empowering leadership proven to play an important role in improving innovative work behavior through strengthening individual psychological resources and organizational capabilities. However, there are still research gaps related to the integration of communication and digitalization factors, the developing country context, and the use of longitudinal and cross-sectional research designs mixed methods. Future research needs to develop a more comprehensive model to explain the relationship between empowering leadership and innovative work behavior in the era of digital transformation.